“He Tells People That I Am Going to Kill My Children”: Post-Separation Coercive Control in Men Who Perpetrate IPV - Tutty, Leslie M. (Violence against women, 2024)
Relatively little research has examined men's use of coercive controlling tactics against female partners after separation. This mixed-methods secondary analysis of 346 Canadian women documented coercive controlling tactics used by their ex-partners (86.4% identified at least one). The composite abuse scale emotional abuse subscale and women being older were associated with men using coercive control tactics post-separation. A secondary qualitative analysis of in-depth interviews with a sub-sample of 34 women provided additional examples. Abusive partners used numerous strategies to coercively control their ex-partners by stalking/harassing them, using financial abuse and discrediting the women to various authorities. Considerations for future research are presented.